Fetal Alcohol Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Hearing and speech and language development in 14 children with fetal alcohol syndrome were evaluated at the Fetal Alcohol Research Center, Wayne State University School of Medicine, Detroit, Michigan, and the Audiology Division, School of Medicine, University of Colorado Health Sciences Center, Denver, Colorado.